2001
DOI: 10.1046/j.1035-6851.2001.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal fume fever: A case report and literature review

Abstract: Metal fume fever is a relatively uncommon presentation to the emergency department. Resulting from inhalation of metal oxides, it presents as an acute, self‐limiting, flu‐like symptom complex often misdiagnosed as a viral illness. We report a case of a 26‐year‐old male presenting with metal fume fever 4 h after oxycutting galvanized steel. The literature is reviewed with respect to pathogenesis, the common presenting symptom complex, investigations and current accepted management of metal fume fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The latter is seen in workers chronically exposed to high levels of airborne Zn (e.g. during galvanization of iron, welding and manufacture of brass) [220]. Interestingly, instillation of Zn salts into the mouse lung induced necrosis of Type 1 alveolar epithelial cells followed by inflammation and elevation of protein levels in BALF over a 2-week period [221].…”
Section: Zinc Supplementationmentioning
confidence: 97%
“…The latter is seen in workers chronically exposed to high levels of airborne Zn (e.g. during galvanization of iron, welding and manufacture of brass) [220]. Interestingly, instillation of Zn salts into the mouse lung induced necrosis of Type 1 alveolar epithelial cells followed by inflammation and elevation of protein levels in BALF over a 2-week period [221].…”
Section: Zinc Supplementationmentioning
confidence: 97%
“…In the absence of intact epithelial barrier, the airway lumen may contain harmful substances, which could initiate inflammatory reactions in the submucosa (1)(2)(3). Exposure to high concentration of zinc in the air may cause significant health risk (4). Zinc toxicity can cause acute respiratory tract inflammation together with bronchial hyper-responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Metal fume fever is a flu-like occupational disease caused by the inhalation of metal fumes, which contain such metals as Zn, Mn, Cu, Cd, Ni, and Al, and which leads to respiratory and systemic syndromes that often occur in workers exposed to metal fumes when welding galvanized metal and melting metal 2 3 4 . Metal fume fever is considered to be a reversible symptom after exposure; however, increasing clinical evidence has found that exposure to metal fumes results in adverse health effects 5 6 . For example, workers using an acetylene torch to dismantle galvanized steel in a poorly ventilated area were diagnosed with diffuse alveolar damage to the lungs 5 .…”
mentioning
confidence: 99%